Faktor-Faktor Yang berhubungan Dengan Kejadian Unmet Need Pada Wus Di Desa Blang Keutumba Kecamatan Juli Kabupaten Bireuen Tahun 2022 - Wildatul Ahya; Nova Khairunnisa; Ghazali Amin (Journal of Health and Medical Science, 2023)
The data obtained at Blang Keutumba still have problems with unmet need in using contraception caused by a lack of knowledge, a lack of awareness of mothers in the data on women of childbearing age in Blang Keutumba Village. The aim of this study was to determine the factors related to the occurrence of unmet need. In Wus in Blang Keutumba Village, Juli District, Bireuen Regency in 2022. This research was conducted using a descriptive analytic method with a Cross Sectional design. The population in this study were all married women of childbearing age aged 20-40 years, namely 418 WUS. Sampling in this study used the Slovin formula, a sample of 81 respondents. Data collection was carried out for 1 week from 9-15 June 2022 by distributing questionnaires. Data analysis used the chi-square statistical test with the STATA program version 14.0. The results showed that there was a relationship between mother's knowledge with unmet need (p-value = 0.038), there is no relationship between husband's work and unmet need (p-value = 0.466), there is a relationship between husband's support and unmet need (p-value = 0.020), there is no relationship the role of health workers with the incidence of unmet need (p-value = 1,000).